VOLUME 2, NO 1 (2014) - Editor In Chief (ARO-The Scientific Journal of Koya University, 2016)
You are now holding the 2nd issue of Aro the Scientific Journal of Koya University. Aro is a newly established journal with ambition to become a globally recognized scientific journal with wider local impact. The editorial team is determined to keep the path of such a mission and sustain Aro’s future publication.